Peran Kepala Madrasah Ibtidaiyah al-Huda Sleman Yogyakarta Dimasa Pandemi COVID 19 - Suratiningsih; Slamet Subagya (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2021)
The aim of this research is to determine the role headmaster of Madrasah Ibtidaiyah Al Huda Sleman Yogyakarta in the Covid 19 pandemic. This research is descriptive research. The research subjects are all members of Madrasah Ibtidaiyah Al Huda using random sampling. Data collection techniques are in the form of observations, interviews and documentations. The data analysis used in this research is descriptive qualitative. The results of the study are as follows: First, the headmaster of Al Huda Madrasah Ibtidaiyah has succeeded in motivating teachers and monitoring online learning. Second, the headmaster Madrasah Ibtidaiyah Al Huda has succeeded in providing socialization, guidance and assistance to students while studying at home. Third, the headmaster Madrasah Ibtidaiyah Al Huda succeeded in involving parents, committees, in collaboration with kompita to help parents and surrounding communities in the socio- economic field.